A systematic analysis of the resistance and sensitivity of HER2YVMA receptor tyrosine kinase mutant to tyrosine kinase inhibitors in HER2-positive lung cancer. (2nd January 2016) - Shen, Xiaokun; Chen, Beibei; Ma, Zhaosheng; Xie, Bojian; Cao, Xinguang; Yang, Tiejun; Zhao, Yuzhou; Qin, Jianjun; Li, Jicheng; Cao, Feilin; Chen, Xiaobing
Abstract: Human epidermal growth factor receptor 2 (HER2) has become a well-established target for the treatment of HER2-positive lung cancer. However, a frequently observed in-frame mutation that inserts amino acid quadruplex Tyr776-Val777-Met778-Ala779 at G776 (G776 YVMA ) in HER2 kinase domain can cause drug resistance and sensitivity, largely limiting the application of reversible tyrosine kinase inhibitors in lung cancer therapy. A systematic investigation of the intermolecular interactions between the HER2 YVMA mutant and clinical small-molecule inhibitors would help to establish a complete picture of drug response to HER2 G776 YVMA insertion in lung cancer, and to design new tyrosine kinase inhibitors with high potency and selectivity to target the lung cancer-related HER2 YVMA mutant. Here, we combined homology modeling, ligand grafting, structure minimization, molecular simulation and binding affinity analysis to profile a number of tyrosine kinase inhibitors against the G776 YVMA insertion in HER2. It is found that the insertion is far away from HER2 active pocket and thus cannot contact inhibitor ligand directly. However, the insertion is expected to induce marked allosteric effect on some regions around the pocket, including A-loop and hinges connecting between the N- and C-lobes of HER2 kinase domain, which may exert indirect influence to inhibitor binding. Most investigated inhibitors exhibit weak binding strength to both wild-type and mutant HER2, which can be attributed to steric hindrance that impairs ligand compatibility with HER2 active pocket. However, the cognate inhibitor lapatinib and the non-cognate inhibitor bosutinib were predicted to have low affinity for wild-type HER2 but high affinity for HER2 YVMA mutant, which was confirmed by subsequent kinase assay experiments; the inhibitory potencies of bosutinib against wild-type and mutant HER2 were determined to be IC50 > 1000 and =27 nM, respectively, suggesting that the bosutinib might be exploited as a selective inhibitor for mutant over wild-type HER2. Structural examination revealed that formation of additional non-bonded interactions such as hydrogen bonds and hydrophobic contacts with HER2 A-loop region due to G776 YVMA insertion is the primary factor to improve bosutinib affinity upon the mutation.